Dokončnost mednarodnih investicijskih arbitražnih odločb - Sancin, Vasilka (Podjetje in delo, 2014)
The article addresses the question of finality of arbitral awards in investment disputes, particularly in investor-state arbitrations before the International Centre for Settlement of Investment Disputes (ICSID). They are arguably "automatically" enforceable when they impose the pecuniary obligations, as if they were a final judgment of a court in that State. A detailed overview of the relevant provisions of the ICSID Convention reveals possible alternative interpretations, which are because of its potential impact not irrelevant and thus deserve special attention.
Keywords: arbitraža; arbitražna sodišča; arbitražne odločbe